Religion, National Identity, and Confessional Politics in Lebanon - Rabil, R. author. aut Link
XV, 213 p.
Keywords: Against a background of weak and contested national identity and capricious interaction between religious affiliation and confessional politics, this book illustrates in detailed analysis this "comprehensive" project of Islamism according to its ideological and practical evolutionary change.